2011
DOI: 10.1007/s00417-011-1882-7
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich 61 (CYR61) is up-regulated in proliferative diabetic retinopathy

Abstract: CYR61 are likely to be involved in the pathogenesis of diabetic retinopathy, and may play a role in the course of neovasculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…Despite this, these data indicated that the expression of CCN1 was involved in cell proliferation and apoptosis. These findings are supported by the findings of previous studies, which demonstrated that EC proliferation is the initial step in angiogenesis, and is an essential step prior to both cell migration and tube formation (30).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite this, these data indicated that the expression of CCN1 was involved in cell proliferation and apoptosis. These findings are supported by the findings of previous studies, which demonstrated that EC proliferation is the initial step in angiogenesis, and is an essential step prior to both cell migration and tube formation (30).…”
Section: Discussionsupporting
confidence: 90%
“…Pathological angiogenesis, commonly induced by tissue ischemia, hypoxia or inflammation, underlies numerous vascular disorders, including retinopathy of prematurity, which is a leading cause of blindness in childhood (27). Previous studies have directly (28,29) and indirectly (30,31) demonstrated that CCN1 is able to promote chorioretinal angiogenesis in vitro via the proliferation and migration of ECs, and the formation of tubular structures, indicating that CCN1 may be involved in the formation of angiogenesis in the retina. These processes all begin with EC proliferation and, mechanistically, CCN1 may promote the proliferation of ECs by upregulating the PI3K/Akt pathway (10,11,21).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the levels of CCN1 increased in retinal blood vessels at the early stages of diabetes and in late stages of proliferative disorders in mouse models of diabetic and ischemic angiopathies (13,14). Whether CCN1 expression under pathological conditions recapitulates biological events characteristic of earlier developmental stages, as most fetal genes do, is unknown.…”
mentioning
confidence: 99%
“…Its expression is induced by advanced glycation end products (Hughes et al, 2007). In proliferative diabetic retinal membrane CYR61 is induced in ganglion cells, endothelial cells, and smooth muscle cells, where it may contribute to the loss of normal capillary pericytes by apoptosis (Liu et al, 2008) and enhancement of aberrant neovascularization (Zhang et al, 2012). Elevated CYR61 in vitreous is detected in patients with proliferative diabetic retinopathy (You et al, 2012).…”
Section: Notementioning
confidence: 99%